2014
DOI: 10.4187/respcare.02798
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Exposure to Secondhand Smoke During Pregnancy and Low Birthweight: A Narrative Review

Abstract: Exposure to secondhand smoke (SHS) during pregnancy may have adverse effects on the mother and infant. This study investigates the association of maternal exposure to SHS with low birthweight (LBW) in infants. Smoking during pregnancy has been linked to multiple complications for both mother and infant. To examine association of LBW and environmental tobacco smoke exposure during pregnancy, we reviewed 20 articles. Articles were accessed using the following electronic databases: CINAHL Plus with full text (EBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
(51 reference statements)
1
22
0
4
Order By: Relevance
“…Ціла низка досліджень переконливо дово дить зв'язок паління під час вагітності з наро дженням дітей із малою масою тіла [15,23,24,25,45]. Найчастіше такі малюки наро джувалися у жінок, що палили у першому та другому триместрі вагітності.…”
Section: низька маса тіла дитини при народженні та паління вагітноїunclassified
See 2 more Smart Citations
“…Ціла низка досліджень переконливо дово дить зв'язок паління під час вагітності з наро дженням дітей із малою масою тіла [15,23,24,25,45]. Найчастіше такі малюки наро джувалися у жінок, що палили у першому та другому триместрі вагітності.…”
Section: низька маса тіла дитини при народженні та паління вагітноїunclassified
“…Найчастіше такі малюки наро джувалися у жінок, що палили у першому та другому триместрі вагітності. Тоді як немовля та, матері яких починали палити тільки напри кінці терміну гестації, не мали достовірних роз біжностей у вазі при народженні з дітьми кон трольної групи [15,17]. Цікавим є той факт, що народження дітей з низькою масою тіла достовірно частіше відмічалося серед жінок, які зазнавали впливу тютюнового диму пасивно, а не палили самі, що підтверджує негативний вплив навіть малих доз токсичних речовин, які виділяються під час цього процесу [21].…”
Section: низька маса тіла дитини при народженні та паління вагітноїunclassified
See 1 more Smart Citation
“…[10] The escalating numbers of smokers cause grave complications in both pregnant women and infants by passive tobacco exposure. [11][12][13] Studies have stated that although many pregnant women never smoke, they still have great chances to expose to SHS and THS, [14] especially smoking from their spouses. A study in Sichuan province, China, has shown that 75.1% of non-smoking pregnant women are victimized due to chronic smoking habits of respective spouses.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of passive smoking leading to pregnancy complication and mortality is well documented (12)(13)(14). Cigarette smoke contains more than 3000 toxic substances that result in damage of the placenta particularly in the membrane compartments (15).…”
Section: Introductionmentioning
confidence: 99%